A Comparison of UAF and SysML-Based DODAF Implementations for Cybersecurity Architecture Modeling - Green, Christopher (Cybersecurity and Innovative Technology Journal, 2026)
IoT systems with constrained resources are moving towards energy harvesting to ensure sustainable and autonomous operations in resource-limited environments. Yet, incorporating energy harvesting in such a system involves intricate dependencies between energy production, energy storage capabilities, system operation, security controls, and availability considerations at a mission level. Current practices focus on analyzing the mentioned dependencies for individual components/subsystems without accounting for potential cross-domain effects, thus leaving open room for potential errors in system-level integration. In this paper, we propose an architecture-driven approach for integrating energy harvesting based on the Unified Architecture Framework (UAF). Energy availability is considered from the perspective of a system-level architectural constraint within a framework based on a meta-model, instead of being just a design consideration. Capabilities, operations, resources, security, and standards-related concepts are materialized within a common semantic baseline to enable cross-domain traceability of the dependencies between energy, security, and missions. Variability in the energy produced by the energy harvesters propagates through operations, communications, and security controls up to capabilities realization and availability. This technique takes advantage of the relationships between domains provided by the UAF Domain MetaModel to achieve structured dependency propagation and systematic trade-space analysis between domains. It is clear from the findings that integrating energy and cybersecurity elements into a single architectural framework helps minimize fragmentation in integration, enhances system-level reasoning, and facilitates energy-conscious co-design of operations and security functions.